MAINTENANCE PADA VERTICAL RAW MILL CK-310 TIPE ROLLER MILL PLANT - 10 - Nurbaiti, Nurbaiti; Hoten, Hendri Van (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2025)
A vertical raw mill is one of the main tools in cement production, which functions as a material grinder measuring from 5-7 cm to 90 microns. The tool also performs in the drying process of raw materials to reduce the water content before entering the suspension preheater section. The maintenance process on the vertical raw mill is carried out while the machines are operating. The maintenance is used to prevent and predict the production machine. The method is inspection using an infrared thermometer and vibrascanner. Test results show that the vertical raw mill can operate normally.